Abnormal expression of BAFF and its receptors in peripheral blood and skin lesions from systemic lupus erythematosus patients - Yongjian Chen; Ming Yang; Di Long; Qianwen Li; Ming Zhao; Haijing Wu; Qianjin Lu (Taylor & Francis Group, 2020)
Systemic lupus erythematosus (SLE) is an autoimmune disease that is characterized by abnormal T and B cells. B-cell activating factor (BAFF) has been suggested to play a crucial role in lupus by promoting the proliferation, differentiation, and survival of B cells. Increased serum levels of BAFF have been found in patients with lupus. However, the expression of BAFF and its receptors on immune cells and in skin has not been systematically reported before. Here, we report that SLE patients showed increased levels of BAFF on circulating CD3+ T cells and B-cell maturation antigen (BCMA) on CD14+ monocytes and dramatically increased expression of BAFF in lupus skin lesions compared with those of healthy controls. TACI was undetectable on circulating immune cells. An increased serum level of BAFF was also confirmed in lupus patients in this study. Our findings may provide a better understanding of the pathogenesis and predictors of BAFF antibody treatment response, as well as potential targets for skin therapies.